2015
DOI: 10.1177/2277975215587814
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying: A Review of the Defining Features, Measurement Methods and Prevalence across Continents

Abstract: Over the past 25 years, academic researchers across the globe have extensively studied the concept, definition and the prevalence of workplace bullying. Even though researchers around the globe explain bullying with multiple terminologies, certain key features define the phenomenon. The researchers have used various methods and tools to measure the prevalence of the phenomenon. Therefore, this article aims to review and present the key defining features, various measuring methods and the prevalence of workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The total prevalence of workplace bullying was 39.1% and 58.9% for the last 12 months and at some point in their working life, respectively. In Ciby and Raya’s (2015) review, they reported that the highest prevalence of workplace bullying was found in Asia (over 52% in Turkey and Pakistan) [ 35 ]. Although it is difficult to compare the prevalence rates due to the use of different measurement methods, tools, and operational criteria [ 36 ], our results are concerning as the rates are more than double the global prevalence rate of 15% [ 37 , 38 ], suggesting that the issue must be addressed urgently.…”
Section: Discussionmentioning
confidence: 99%
“…The total prevalence of workplace bullying was 39.1% and 58.9% for the last 12 months and at some point in their working life, respectively. In Ciby and Raya’s (2015) review, they reported that the highest prevalence of workplace bullying was found in Asia (over 52% in Turkey and Pakistan) [ 35 ]. Although it is difficult to compare the prevalence rates due to the use of different measurement methods, tools, and operational criteria [ 36 ], our results are concerning as the rates are more than double the global prevalence rate of 15% [ 37 , 38 ], suggesting that the issue must be addressed urgently.…”
Section: Discussionmentioning
confidence: 99%
“…While research on the association between societal gender equality and school climate is scarce, research has pointed out that educational systems in feminine cultures tend to value social adaptation (rather than academic performance), friendliness in teachers (rather than their brilliance), and mutual solidarity (rather than competition) (Hofstede et al 2010). Negative social behaviors, such as bullying, are less common (Inchley et al 2016) and appear to be less accepted (Ciby and Raya 2015; Hofstede et al 2010) in countries with feminine cultures, compared to masculine cultures. Importantly, the characteristics of the school climate on which countries with feminine cultures score typically higher (i.e., high teacher and classmate support), have been consistently associated with better mental health outcomes in adolescents (García-Moya et al 2015; Ottova et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the changing corporate culture in Indian firms marked by increased workplace pressure and highly competitive work environments also directly or indirectly relates to onset as well as the promotion of bullying acts (Rai & Agarwal, 2017c). D'Cruz (2015), Ciby and Raya (2015), and Agarwal (2016, 2017a) are few of the Indian researchers involved in studying workplace bullying. Recent studies (D'Cruz & Rayner, 2013;Rai & Agarwal, 2017b) and popular surveys (e.g., ASSOCHAM, 2012;Job Portal Career Builder, 2014) have ascertained a high prevalence of bullying in Indian organizations (42-55%).…”
Section: Discussionmentioning
confidence: 99%